KONTRIBUSI PROFITABILITAS TERHADAP PERTUMBUHAN LABA PT. BANK RAKYAT INDONESIA (PERSERO), TBK - Wulan Purnama Rais; Nur Fiskayani Yustika; Adhe Alda Rezky Darmawan; Muhammad Irfai Sohilauw (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this study is to examine and evaluate the impact of return on assets (ROA), return on equity (ROE), and net profit margin (NPM) on PT. Bank Rakyat Indonesia (Persero), Tbk's profit growth. The method of explanatory analysis with a quantitative approach is used in this study. From 2010 to 2019, secondary data were analyzed quarterly, yielding 40 observations. The data was analyzed with Microsoft Excel 2013 and SPSS Version 21. Using multiple linear regression analysis, Return On Assets (ROA) / X1 had a negative and insignificant effect on Profit Growth (Y) of PT. Bank Rakyat Indonesia (Persero), Tbk from 2010 to 2019. However, Return On Assets (ROE) / X2 and Net Profit Margin (NPM) / X3 have a positive and significant impact on Changes in Profit (Y) PT. Bank Rakyat Indonesia (Persero), Tbk from 2010 to 2019.